Extensive fibrosis caused by Pleural Tuberculosis: A lesson from a case without post‐exposure‐prophylaxis1. Issue 2 (15th May 2012) - Emmrich, Julius Valentin; Kamprad, Manja; Sorge, Ina; Hammerschmidt, Stefan; Gradistanac, Tanja; Schille, Regine; Kiess, Wieland; Prenzel, Freerk
Abstract We report the case of a 9‐year‐old boy with extensive pleural fibrosis and contraction of the affected hemithorax secondary to pleural tuberculosis (TB), who was successfully treated with a 6 months course of the standard WHO regimen. Although well described for the adult population, this complication is rare among children and to our knowledge, no such case has been described since the widespread introduction of antitubercular therapy in the 1950s. This case underscores the importance of appropriate follow‐up and administration of chemoprophylaxis after TB exposure. Pediatr Pulmonol. 2013; 48:206–209. © 2012 Wiley Periodicals, Inc.